Leadership Model for General Education Administration in Islamic Private Schools - PRIYAKORN, FATIMA; Suvarnasara, Chainarong; Pattrawiwat, Kanchana (KASEM BUNDIT JOURNAL, 2019)
The objectives of this research were 1) to develop the leadership model for the general education administrators of Islamic Private Schools and 2) to verify the validity of the model. The sample was 226 school administrators. The questionnaire was used to gather data, and descriptive statistics were used to analyze the frequency distribution of the variable background of the sample and to validate the model by confirmatory factor analysis. The main findings were 1) The leadership model for the general education administrators of Islamic Private Schools consisted of three aspects, namely: 1.1) The trait of administrator which was composed of vision, intelligence, responsibility, collaboration, and being accepted, 1.2) Skill of the school administrator which was composed of administration skill, communication skill, human resource skill, transformation skill, innovation, and technology skill, and 1.3) adherence to religion which was composed of Islamic practicing, devoting themselves for society, and being role models, and 2) The leadership model for the general education principal of Islamic Private Schools consistent with the empirical data with the goodness of fit statistics. The value for a Chi-square was 53.83 with 62 degrees of freedom (df = 62; p = 0.76504). The goodness of Fit Index (GFI) was 0.965 whereas the Adjusted Goodness of Fit Index (AGFI) was 0.949. The Root Mean Square Residual (RMR) was 0.006.